Elastosonographic Evaluation of Endometrium in Postmenopausal Bleeding - İsmail Burak Gültekin; Orhan Altınboğa; Serap Gültekin; Elif Akkaş Yılmaz; Gökşen İnanç İmamoğlu; Afra Alkan; Tuncay Küçüközkan (Medical Network, 2016)
OBJECTIVE: The aim of this study was to evaluate the elastosonographic changes of endometrium in postmenopausal women with uterine bleeding. STUDY DESIGN: A total of 80 women in their postmenopausal period were enrolled for the study; 19 with postmenopausal bleeding and 61 normal healthy controls. All patients with a history of previous uterine surgery (including myomectomy) and/or endometrial interventions such as endometrial ablation, polyp removal, hysteroscopic interventions (except solely diagnostic procedures) and endometrial sampling within one year were excluded from the study because of the possibility of endometrial changes that may interfere with elastosonographic starin ratios. B-mode scanning, Doppler and real-time tissue elastography (RTE) were performed by the same single operator, blinded to the study design. The ultrasonographic findings (strain ratio, endometrial thickness, uterine artery Doppler indices) were evaluated between groups. RESULTS: The means of age were 57.84±5.36 years and 56.34±3.32 years for the study group and the controls respectively. The groups were similar in regard to age (p=0.328). The parity of the postmenopausal bleeding group was significantly higher than the controls (p<0.001). When uterine artery Doppler indices were compared between groups, study group was found to have lower values in regard to controls (p<0.001). The medians of endometrial thickness were 4.30 (IQR=3.80)mm in the study group and 2.60 (IQR=0.90) mm in the control group and the difference was found to be significant (p<0.001). The medians of elastosonographic B/A ratios were 0.98 (IQR=0.18) and 1.27 (IQR=1.78) for the study group and controls respectively. The B/A ratios were found to be significantly lower in the study group (lower tissue elasticity) (p<0.001). CONCLUSION: Tissue biopsy for histopathologic evaluation is still the gold standart in cases with postmenopausal bleeding. However, the need for a noninvasive method with high sensitivity and specificity is still under search. Some women who had been offered biopsy but did not accept the intervention because of the invasive nature of the procedure will be eft undiagnosed for a possible malignancy. Evaluation of the endometrium with real-time tissue elastosonography is one of the noninvasive methods with this potential and the diagnostic value of RTE could be possible with multicentric studies including more subjects.